2005
DOI: 10.1007/s00220-005-1401-y
|View full text |Cite
|
Sign up to set email alerts
|

Solvability of the Hamiltonians Related to Exceptional Root Spaces: Rational Case

Abstract: Solvability of the rational quantum integrable systems related to exceptional root spaces G 2 , F 4 is re-examined and for E 6,7,8 is established in the framework of a unified approach. It is shown the Hamiltonians take algebraic form being written in a certain Weyl-invariant variables. It is demonstrated that for each Hamiltonian the finite-dimensional invariant subspaces are made from polynomials and they form an infinite flag. A notion of minimal flag is introduced and minimal flag for each Hamiltonian is f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(68 citation statements)
references
References 22 publications
6
62
0
Order By: Relevance
“…[14] to obtain the energy eigenvalues in (14) and (15) by purely algebraic means. We also mention that our point of view is closely related to the theory of quasi-exactly solvable Schrödinger operators; see, e.g., [4,15]. Moreover, the identities which are the key to our results are stated in Corollaries 2.2 and 2.3 below, and they were known before only in special cases: an important special case of these identities for the Sutherland model (case II) is a consequence of a well-known result on Jack polynomials which, to our knowledge, is due to Stanley (see Proposition 2.1 in [49]), and a generalisation of the latter to the deformed case and other non-deformed cases can be found in [48] and [13,39,45], respectively.…”
Section: Construction Methodmentioning
confidence: 99%
“…[14] to obtain the energy eigenvalues in (14) and (15) by purely algebraic means. We also mention that our point of view is closely related to the theory of quasi-exactly solvable Schrödinger operators; see, e.g., [4,15]. Moreover, the identities which are the key to our results are stated in Corollaries 2.2 and 2.3 below, and they were known before only in special cases: an important special case of these identities for the Sutherland model (case II) is a consequence of a well-known result on Jack polynomials which, to our knowledge, is due to Stanley (see Proposition 2.1 in [49]), and a generalisation of the latter to the deformed case and other non-deformed cases can be found in [48] and [13,39,45], respectively.…”
Section: Construction Methodmentioning
confidence: 99%
“…(1,2,3) n for any n ∈ N and therefore they preserve the flag P (1,2,3) . The second class operators (raising operators) act on the space P…”
Section: Hidden Algebramentioning
confidence: 99%
“…It can be shown that the Hamiltonian h H 3 has a certain degeneracy -it preserves two different flags: one with minimal characteristic vector (1,2,3) and another one with characteristic vector (1,3,5). The fact that the operator h H 3 with coefficients (20) commutes with f given by (31) implies that common eigenfunctions of the operators h H 3 and f are elements of the flag of spaces P (1,3,5) .…”
Section: Integralmentioning
confidence: 99%
See 2 more Smart Citations